Analisis Tingkah Laku Bullying Verbal dengan Teman Kelas Siswa di SMA Negeri 8 Palembang - Aprilia, Nyimas Eva (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2019)
Verbal bullying is a verbal act which is the easiest to do and is not seen directly but has a serious impact. Verbal bullying can take the form of nicknames, reproaches, slanders, cruel criticisms and insults. Based on the findings when observing at SMA Negeri 8 Palembang, there were some students who did often carry out bullying to their classmates such as scoffing, making name calls, ridiculing, and so on, furthermore make the students who are the victims of bullying feel scared to enter the classroom and feel they do not have friend in their class. This study uses a qualitative method. This type of research is descriptive qualitative. The source of information in this study were 9 students who did verbal bullying. The results showed that in general the perpetrators carried out verbal bullying against their classmates because it was done to show resistance or aggressive attitudes towards the victim caused by the negative behaviors of the victim. Based on the results of the study, it can be suggested to the teachers to be able to plan services to prevent bullying.Keyword :Verbal Bullying